2023
DOI: 10.1108/sampj-11-2022-0605
|View full text |Cite
|
Sign up to set email alerts
|

Are ESG performance-based incentives a panacea or a smokescreen for excess compensation?

Abstract: Purpose This paper aims to examine how the use of environmental, social and governance (ESG) incentives intersects with top management power and various corporate governance mechanisms to affect excess annual cash bonus compensation. Design/methodology/approach The authors use a novel artificial intelligence (AI) technique to obtain data about ESG incentives use by firms in the S&P 500. The authors test the hypotheses with an endogenous treatment-regression and a contrast test. Findings When the top ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 57 publications
(93 reference statements)
0
0
0
Order By: Relevance
“…These findings support the findings of a study by Lu, Kang, and Tseng [34], which indicates that offering competitive pay would have an effect on raising employee performance. According to Keddie and Magnan [35], pay is crucial in fostering an employee's commitment to their task. According to research by Fauzan [12]; Chouaibi, Rossi & Zouari [36], the findings show that compensation can foster or increase employee needs and that it must be given in accordance with the proper procedure to prevent employee inequality.Additionally, it was shown that pay and job motivation had a significant impact on employees' performance.…”
Section: Resultsmentioning
confidence: 99%
“…These findings support the findings of a study by Lu, Kang, and Tseng [34], which indicates that offering competitive pay would have an effect on raising employee performance. According to Keddie and Magnan [35], pay is crucial in fostering an employee's commitment to their task. According to research by Fauzan [12]; Chouaibi, Rossi & Zouari [36], the findings show that compensation can foster or increase employee needs and that it must be given in accordance with the proper procedure to prevent employee inequality.Additionally, it was shown that pay and job motivation had a significant impact on employees' performance.…”
Section: Resultsmentioning
confidence: 99%